Efek Protektif Andrografolid terhadap Kejadian Kardiotoksisitas Pasca Aplikasi Doksorubisin pada Tikus - Sri Wahyuni Salam; Agus Setiyono; Vetnizah Juniantito (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2016)
Cardiotoxicity is one of the important side effects of doxorubicin, an anthracycline antibiotic and chemotherapeutic drug. The aim of this study was to explore the potential protective effect of andrographolide (Andro), an anti-inflammatory and anti-oxidant agents, against cardiotoxicity induced by doxorubicin (DXR). Thirty Sprague Dawley rats (80-100 g) were divided into four groups: (a) Control (b) DXR (4 mg/kg intraperitoneally (IP) were made weekly for 4 weeks), (c) DXR+Andro20 (low dose andro; 20 mg/kg IP weremade daily for 4 weeks, 24 h after DXR), (d) DXR+Andro100 (high dose andro; 100 mg/kg IP were made daily for 4 weeks, 24 h after DXR). Furthermore, at the end of experimental period, all rats were euthanized and hearts were removed for hispatological analyses. Hematoxylin-eosin (HE) and Masson Trichrome (MT) staining were used to observe the histomorphological alterations and fibrosis of hearts, respectively. Our results showed that andrographolide treatment (20 mg/kg) augmented the detrimental effects of DXR such as decreased body weight and heart weight, as compared with those in DXR-treated rats. Histopathologically, heart tissue from control group showed compact myocardial architecture without any noticeable lesions. Histopathological analysis fromDXR group showed severe inflammation and fibrosis, whereas DXR+Andro20 group showed almost normal heart morphology. Andrographolide at a dosage of 100 mg/kg did not show protective effects against doxorubicin,and even aggravated myocardial inflammation, as compared with DXR-treated rats. These results indicate that low dose of andrographolide compromised doxorubicin-induced decreased body weight, heart inflammation, andfibrosis.